To cut a long story short: formal chronological modelling for the Late Neolithic site of Ness of Brodgar, Orkney - Card, N; Mainland, I; Timpany, S; Towers, R; Batt, C; Ramsey, C; Dunbar, E; Reimer, P; Bayliss, A; Marshall, P; Whittle, A (Cambridge University Press, 2017)
In the context of unanswered questions about the nature and development of the Late Neolithic in Orkney, we present a summary of research up to 2015 on the major site at the Ness of Brodgar, Mainland Orkney, concentrating on the impressive buildings. Finding sufficient samples for radiocarbon dating was a considerable challenge. There are indications, from both features and finds, of activity pre-dating the main set of buildings exposed so far by excavation. Forty-six dates on thirty-nine samples are presented and are interpreted in a formal chronological framework. Two models are presented, reflecting different possible readings of the sequence. Both indicate that piered architecture was in use by the thirtieth century cal bc and that the massive Structure 10, not the first building in the sequence, was also in existence by the thirtieth century cal bc. Activity associated with piered architecture came to an end (in Model 2) around 2800 cal bc. Midden and rubble infill followed. After an appreciable interval, the hearth at the centre of Structure 10 was last used around 2500 cal bc, perhaps the only activity in an otherwise abandoned site. The remains of some 400 or more cattle were deposited over the ruins of Structure 10: in Model 2, in the mid-twenty-fifth century cal bc, but in Model 1 in the late twenty-fourth or twenty-third century cal bc. The chronologies invite comparison with the near-neighbour of Barnhouse, in use from the later thirty-second to the earlier twenty-ninth century cal bc, and the Stones of Stenness, probably erected by the thirtieth century cal bc. The Ness, including Structure 10, appears to have outlasted Barnhouse, but probably did not endure as long in its primary form as previously envisaged. The decay and decommissioning of the Ness may have coincided with the further development of the sacred landscape around it; but precise chronologies for other sites in the surrounding landscape are urgently required. The spectacular feasting remains of several hundred cattle deposited above Structure 10 may belong to a radically changing world, coinciding (in Model 2) with the appearance of Beakers nationally, but it was arguably the, by now, mythic status of that building which drew people back to it